Analytically continued Fock space multireference coupled-cluster theory: application to the (2)Pi(g) shape resonance in e-N-2 scattering - Sajeev, Y; Santra, R; Pal, S (Journal of Chemical Physics, 2005)
The technique of Fock space multireference coupled-cluster (FSMRCC) is applied for the first time to the correlated calculation of the energy and width of a shape resonance in an electron-molecule collision. The procedure is based upon combining a complex absorbing potential with FSMRCC theory. Accurate resonance parameters are obtained by solving a small non-Hermitian eigenvalue problem. The potential-energy curve of the (2)Pi(g) state of N-2(-) is calculated using the FSMRCC and multireference configuration-interaction (MRCI) level of theories. Comparison with the single-determinant Hartree-Fock theory indicates that correlation effects are important in determining the behavior of the resonance state. (C) 2005 American Institute of Physics.

Correlated complex independent particle potential for calculating electronic resonances - Sajeev, Y; Santra, R; Pal, S (Journal of Chemical Physics, 2005)
We have formulated and applied an analytic continuation method for the recently formulated correlated independent particle potential [A. Beste and R. J. Bartlett J. Chem. Phys. 120, 8395 (2004)] derived from Fock space multireference coupled cluster theory. The technique developed is an advanced ab initio tool for calculating the properties of resonances in the low-energy electron-molecule collision problem. The proposed method quantitatively describes elastic electron-molecule scattering below the first electronically inelastic threshold. A complex absorbing potential is utilized to define the analytic continuation for the potential. A separate treatment of electron correlation and relaxation effects for the projectile-target system and the analytic continuation using the complex absorbing potential is possible, when an approximated form of the correlated complex independent particle potential is used. The method, which is referred to as complex absorbing potential-based correlated independent particle (CAP-CIP), is tested by application to the well-known (2)Pi(g) shape resonance of e-N-2 and the B-2(2g) shape resonance of e-C2H4 (ethylene) with highly satisfactory results. (c) 2005 American Institute of Physics.

General formalism of the Fock space multireference coupled cluster method for investigating molecular electronic resonances - Sajeev, Y; Pal, S (Molecular Physics, 2005)
Electron correlation and relaxation effects play a substantial role in the formation and decay of resonance states. In this paper we formulate a complex absorbing potential combined with the Fock space multireference coupled cluster method for the correlated calculations of resonance energy and width. This can describe the dynamic and non-dynamic electron correlation efficiently in the ionized or electron attached states.
Keywords: electronic resonances; Fock space multireference coupled cluster method

Optimization of nonlinear optical properties by substituent position, geometry and symmetry of the molecule: an ab initio study - Davis, D; Sreekumar, K; Sajeev, Y; Pal, S (Journal of Physical Chemistry B, 2005)
Static polarizability and first- and second-order hyperpolarizability tensors are computed at the correlated level for a series of para-nitroaniline derivatives. The importance of including electron correlation effects in the determination of equilibrium structure and the molecular properties is investigated. A qualitative description of the substitution effects, planarity, and symmetric effect of the molecule on the molecular susceptibility is discussed.